Step-by-step explanation:
wapsi ki Vidya kya hai Hindi mein
-5x + y = -5.....multiply by -2
-4x + 2y = 2
---------------
10x - 2y = 10 (result of multiplying by -2)
-4x + 2y = 2
-----------------add
6x = 12
x = 12/6
x = 2
-5x + y = -5
-5(2) + y = -5
-10 + y = -5
y = -5 + 10
y = 5
solution is (2,5)
Answer:
sin( -∅ )
- 1 / csc ( ∅ )
1 / csc ( -∅ )
Step-by-step explanation:
Since sin(x) is and odd function (a function where f(-a) = f(a) ).
-sin( ∅ ) = sin( -∅ )
On the other hand, we know that sin( ∅ ) = 1 / csc ( ∅ )
Another odd function, so the same as before applies.
-sin( ∅ ) = -1 / csc ( ∅ )
-sin( ∅ ) = 1 / csc ( -∅ )
Standard form for y+7=-2/5(x-10) is y=-7-2/5(x-10)